2005
DOI: 10.1017/s0952523805226044
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the retinal degeneration in three strains of mice carrying the rd-3 mutation

Abstract: Retinal development in 3 strains of rd-3/rd-3 mutant mice, previously shown to have different rates of degeneration, was studied using light, electron, and immunofluorescence microscopy. The time course and phenotype of the degeneration as well as details on the mechanism of massive photoreceptor cell loss are compared with other known retinal degenerations in mice. Up until postnatal day (P) 10, the retinas of all three strains (RBF, 4Bnr, In-30) develop similarly to those of pigmented and nonpigmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…Consistently, the retina of the animal develops normally but both rod and cone photoreceptors start degenerating by postnatal day 14 - i.e. when eyes open – and the degeneration is almost complete by the age of 2–4 months [21], [38], [44]. Similarly, the rd3 frameshift mutation (p.Pro139Alafs*) of the rcd2 collie [40] is likely to produce an unstable, non-functional rd3 protein leading to the loss of GC expression and trafficking.…”
Section: Discussionmentioning
confidence: 82%
“…Consistently, the retina of the animal develops normally but both rod and cone photoreceptors start degenerating by postnatal day 14 - i.e. when eyes open – and the degeneration is almost complete by the age of 2–4 months [21], [38], [44]. Similarly, the rd3 frameshift mutation (p.Pro139Alafs*) of the rcd2 collie [40] is likely to produce an unstable, non-functional rd3 protein leading to the loss of GC expression and trafficking.…”
Section: Discussionmentioning
confidence: 82%
“…Activation of Müller glial cells, reflected by increased GFAP immunoreactivity, is an early feature of the degeneration. This is a common occurrence in degenerating retinas 23, 42–44 and is likely to be secondary to photoreceptor loss; a recent study indicated that damaged photoreceptors release endothelin 2, which in turn stimulates the reactivity of Müller glia. 45 …”
Section: Discussionmentioning
confidence: 99%
“…The rate of degeneration varies with the background strain (Linberg et al, 2005; Friedman et al, 2006; Danciger et al, 2008; Molday et al, 2013). The albino RBF/DnJ strain shows the fastest rate of degeneration with only a monolayer of photoreceptor nuclei present 8 weeks after birth.…”
Section: Truncation Mutations In Rd3 Cause Photoreceptor Degenerationmentioning
confidence: 99%